Literature Review: Analysis to Reduce Maternal Mortality - Indah lestari; Noer Saudah; Catur Prasastia Lukita Dewi (STIKes Patria Husada Blitar, 2022)
The maternal mortality rate in Indonesia is still high. Hard efforts are needed so that the Sustainable Development Goals target of 70 per 100,000 live births in 2030 can be achieved. The purpose of the study was to identify aspects related to the trend issue of maternal mortality, the determinants of causes, strategic efforts and the role of family planning in reducing maternal mortality. This literature review describes sixteen peer-reviewed journals based on inclusion criteria. The results of the analysis of the literature review found that aspects of findings related to maternal mortality were as follows: trends issue maternal mortality (Maternal mortality is more common in developing countries), causative factors (Status health (nutrition, comorbidities and maternal complications), reproductive status (age, parity, gestational distance), access to health services and policies/regulations, health behavior (contraception use, socioeconomic)), strategic efforts (maternal and neonatal health management, Quality antenatal services, safe delivery and family planning) and family plans (Support system (women's status, family and community status)). The review analysis provides directions and patterns of strategic work steps, collaboration of various support systems ranging from the role of individuals, families, communities, health services and the government in ensuring maternal and child health.